2022
DOI: 10.1177/13591053221089104
|View full text |Cite
|
Sign up to set email alerts
|

Improving older adults’ vaccination uptake: Are existing measures of vaccine hesitancy valid and reliable for older people?

Abstract: We sought to establish whether two recently developed measures, the 5C scale and the Vaccination Attitudes Examination (VAX) were reliable and valid for use with older adults. A total of 372 UK-dwelling participants (65–92 years, M = 70.5 years, SD = 4.6) completed a cross-sectional survey measuring health and socio-demographic characteristics in relation to vaccine uptake for influenza, pneumococcal and shingles. The 5C and VAX scales were administered to test their reliability, validity and dimensionality. B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Studies show that older people like to be vaccinated more than younger ones [ 3 , 6 ]. However, vaccination rates during COVID-19 among the 65+ age population have been found to fall below the World Health Organization’s target of 75% in the U.K. [ 7 ], and in Singapore, the elderly were less likely to be vaccinated with the COVID-19 vaccine than young people [ 8 ]. Studies with older adults showed that their willingness to be vaccinated could also be related to the vaccine characteristics [ 9 , 10 ], their perceived risks [ 11 , 12 , 13 ], their health-related behavior [ 11 , 14 ], and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that older people like to be vaccinated more than younger ones [ 3 , 6 ]. However, vaccination rates during COVID-19 among the 65+ age population have been found to fall below the World Health Organization’s target of 75% in the U.K. [ 7 ], and in Singapore, the elderly were less likely to be vaccinated with the COVID-19 vaccine than young people [ 8 ]. Studies with older adults showed that their willingness to be vaccinated could also be related to the vaccine characteristics [ 9 , 10 ], their perceived risks [ 11 , 12 , 13 ], their health-related behavior [ 11 , 14 ], and other factors.…”
Section: Introductionmentioning
confidence: 99%